Role of Institutional Zakat Management of Bangladesh in Recipients’ Income Generation - Md. Muhibur Rahman (Universitas Pembangunan Nasional Veteran Jakarta, 2024)
The majority of Muslims in Bangladesh distribute zakat individually. Zakat management is conducted in both the public and private sectors. However, there is a significant lack of inclination towards making zakat payments via organizations. This research aims to investigate the role of zakat in generating money via institutional management. This study used a mixed-method approach, including qualitative and quantitative data. A systematic questionnaire survey was conducted on 200 people who received zakat, representing both the institutional and non-institutional sectors. The findings of this research suggest that those who received zakat via institutions had a greater capacity to generate money than those who got zakat through informal means. Several zakat management institutions are helping zakat recipients increase their income by supplying them with income-generating items and a significant quantity of zakat funds. It may be inferred that the proper implementation of institutional zakat management has the potential to enhance the income growth rate of zakat recipients in Bangladesh.